Specific features of the principle of the time-temperature superposition in low density polyethylene filled with shungite - N. N. Komova; E. E. Potapov; E. E. Gruskov; G. E. Zaikov (Тонкие химические технологии, 2013)
The time dependence of the mechanical losses of low density polyethylene (LDPE) filled with fine particles of shungite in the process of periodic dynamic loading at changing frequency of loading and temperature was studied. It was shown that upon increasing the filler concentration and loading frequency these dependences are either similar in nature or shifted in the time-temperature scale on the graphs. The temperature and time dependent parameters and the interpretation of their physical meaning were proposed. It was confirmed that development of relaxation processes occurs in filled polymers under dynamic loading. A relationship between the parameters of these processes is described by logarithmic and exponential functions. These dependencies are determined by both the polymer matrix and the transition polymeric layer formed on the filler surface.